2008
DOI: 10.1007/s10162-008-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Na,K-ATPase α Subunit in the Rat Spiral Ganglion and Organ of Corti

Abstract: Processing of sound in the cochlea involves both afferent and efferent innervation. The Na,K-ATPase (NKA) is essential for cells that maintain hyperpolarized membrane potentials and sodium and potassium concentration gradients. Heterogeneity of NKA subunit expression is one mechanism that tailors physiology to particular cellular demands. Therefore, to provide insight into molecular differences that distinguish the various innervation pathways in the cochlea, we performed a variety of double labeling experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 63 publications
6
105
1
2
Order By: Relevance
“…The selective survival advantage of type II over type I neurons has also been seen in other degeneration models, e.g., in ototoxic lesions (Spoendlin 1975;Lim 1976;Leake and Hradek 1988) transection of the cochlear nerve (Spoendlin 1975). A recent study revealed that differentiated expression patterns of Na,K-ATPase α isoforms are present in types I and II SGNs with Na,K-ATPase, α3 being present in type I SGNs but not in type II neurons (McLean et al 2009). Further studies on the molecular and functional characterization of these two types of neurons are needed to understand their differential response to insults.…”
Section: Type I Sgn Degeneration and Glial Cell Reactivation In Injurmentioning
confidence: 80%
“…The selective survival advantage of type II over type I neurons has also been seen in other degeneration models, e.g., in ototoxic lesions (Spoendlin 1975;Lim 1976;Leake and Hradek 1988) transection of the cochlear nerve (Spoendlin 1975). A recent study revealed that differentiated expression patterns of Na,K-ATPase α isoforms are present in types I and II SGNs with Na,K-ATPase, α3 being present in type I SGNs but not in type II neurons (McLean et al 2009). Further studies on the molecular and functional characterization of these two types of neurons are needed to understand their differential response to insults.…”
Section: Type I Sgn Degeneration and Glial Cell Reactivation In Injurmentioning
confidence: 80%
“…Examination of confocal z-stacks immunostained for a Na/K ATPase expressed by ANF terminals in the IHC area (McLean et al, 2009) suggests that ouabain treatment elicits plasticity in synaptic architecture in addition to simple degeneration of synaptic elements. Most dramatic is the appearance of large nerve terminals (e.g., Fig.…”
Section: Cochlear Histopathologymentioning
confidence: 99%
“…The survival of type-IIs following kainate or acoustic overexposure may arise because these manipulations cause a type of glutamate excitotoxicity, and type-II neurons do not express the same complement of AMPA-type glutamate receptors as type-Is (Pujol et al, 1985;Liberman et al, 2011). The selective survival of the type-II neurons following ouabain may arise because ouabain-elicited neuronal death is due to blockade of the α3 subunit of the Na + /K + ATPase (Azarias et al, 2012), and this subunit is expressed by type-I, and not by type-II, spiral ganglion neurons (McLean et al, 2009). The selective survival of type-II neurons following cochlear nerve transection (Spoendlin and Suter, 1976) is not so easily explainable, and therefore suggests that the type-IIs may be generally more robust, perhaps because of a generally lower level of spike activity (Brown, 1994).…”
Section: Cochlear Neuropathy and Synaptopathy: Ouabain Versus Other Imentioning
confidence: 99%
“…In contrast, other Na,K-ATPase subunit isoforms are expressed in a tissue-specific manner. The ␣ 2 isoform is expressed mainly in muscle and nervous system (1-3, 6, 7); the ␣ 3 isoform is expressed mainly in neurons (8,9), whereas the ␣ 4 isoform is found only in testis (10,11). The ␤ 2 isoform is expressed predominantly in brain and muscle (3,7), whereas the ␤ 3 isoform is mainly expressed in lung, testis, skeletal muscle, and liver (12,13).…”
mentioning
confidence: 99%